OVERCOMING LISTENING PROBLEMS RELATED TO LISTENERS’ PSYCHOLOGICAL CHARACTERISTICS AS A WAY TO ENHANCE GOOD ATTITUDE TOWARD ENGLISH LANGUAGE TEACHING - Dwi Rahayu; Chusna Apriyanti (UAD TEFL International Conference)
This paper aims to know the listening problems related to listeners’ psychological characteristics and the strategies to solve those problems. The researchers used descriptive qualitative research design. The data are collected through observation and giving questionnaire to the students on listening class of English Education Study Program grade I STKIP PGRI Pacitan academic year 2016-2017. The result shows that there are five problems related to psychological characteristic. First, the students feel nervous and worried when they do not understand the spoken text. Second, the students have difficulties in understanding the spoken text, which is of their interest. Third, they stop listening when they have problems in understanding a listening text. Fourth, they feel disappointed when they do not have total comprehension. Fifth, before listening, they fear that they cannot understand the text. Based on these problems, the lecturer gives some solving strategies. First, the lecturer provides the text based on the students’ level and ages. This is also related to the vocabularies ability. Second, the lecturer provides listening tasks that arouse students’ interest. The lecturer gives different inputs, such radio, TV, songs, lectures, advertisement. Third, the lecturer gives extra time in each section to motivate the students in answering the task. Fourth, the lecturer provides listening task’s background knowledge. Besides, the lecturer gives feedback to increase students’ motivation. Fifth, lecturer should encourage their students to develop listening strategies, such as predicting, asking for clarification, and using non-verbal cues to improve learners’ listening comprehension ability.